2012
DOI: 10.1021/mp3002717
|View full text |Cite
|
Sign up to set email alerts
|

Masking and Triggered Unmasking of Targeting Ligands on Liposomal Chemotherapy Selectively Suppress Tumor Growth in Vivo

Abstract: We investigated the feasibility and efficacy of a drug delivery strategy to vascularized cancer that combines targeting selectivity with high uptake by targeted cells and high bioexposure of cells to delivered chemotherapeutics. Targeted lipid vesicles composed of pH responsive membranes were designed to reversibly form phase-separated lipid domains, which are utilized to tune the vesicle's apparent functionality and permeability. During circulation, vesicles mask functional ligands and stably retain their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…[10][11][12][13] Single-positron emission computed tomography/computed tomography studies showed that radioconjugated peptides were able to accumulate specifically at the tumor site, with K d ranging from 30 to 45 nM, with minimal nonspecific retention in other organs. This peptide sequence has also been proposed for the selective delivery of supramolecular carriers such as copolymeric micelles 14 or pH-tunable liposomes 15 for diagnostic or therapeutic applications.…”
Section: Ringhieri Et Almentioning
confidence: 99%
“…[10][11][12][13] Single-positron emission computed tomography/computed tomography studies showed that radioconjugated peptides were able to accumulate specifically at the tumor site, with K d ranging from 30 to 45 nM, with minimal nonspecific retention in other organs. This peptide sequence has also been proposed for the selective delivery of supramolecular carriers such as copolymeric micelles 14 or pH-tunable liposomes 15 for diagnostic or therapeutic applications.…”
Section: Ringhieri Et Almentioning
confidence: 99%
“…During the last three decades, this idea developed into many strategies for construction of pH-sensitive liposomes. One of the major approaches employs an acid-triggered change of interactions between molecules in a mixture of non-polar and anionic lipids that results in phase transition (5) and/ or formation of domains with 'leaky' interfaces (32,33). Variation of the pKa of anionic lipids and their molar ratio can slightly modify the pH sensitivity.…”
Section: Ph-responsive Systemsmentioning
confidence: 99%
“…A plateau is reached, between 5 and 10 mol%, where increasing the surface density no longer achieves greater binding [12]. In addition, vehicles need to balance cell targeting with immune recognition [17,18]. High antibody densities lead to a faster rate of liposome clearance from circulation (above 70e80 mg antibody/mmol phospholipid [19,20]) whereas low densities lack specificity.…”
Section: Introductionmentioning
confidence: 99%